2020
DOI: 10.1021/acs.jpcb.0c08598
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Charge Transport and Base Excision Repair in the MutY–DNA Glycosylase

Abstract: Experimental evidence suggests that DNA-mediated redox signaling between high-potential [Fe4S4] proteins is relevant to DNA replication and repair processes, and protein-mediated charge transfer (CT) between [Fe4S4] clusters and nucleic acids is a fundamental process of the signaling and repair mechanisms. We analyzed the dominant CT pathways in the base excision repair glycosylase MutY using molecular dynamics simulations and hole hopping pathway analysis. We find that the adenine nucleobase of the mismatched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In support of these ideas, previous work has shown that the Fe-S cluster is more easily oxidized when MutY is bound to DNA indicating that alterations resulting from DNA binding impact the Fe–S cluster environment and properties ( 49 ). The mechanism for communication seems to work in both directions as different oxidation states of the cluster appear to be transmitted to the active site and influence adenine excision ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…In support of these ideas, previous work has shown that the Fe-S cluster is more easily oxidized when MutY is bound to DNA indicating that alterations resulting from DNA binding impact the Fe–S cluster environment and properties ( 49 ). The mechanism for communication seems to work in both directions as different oxidation states of the cluster appear to be transmitted to the active site and influence adenine excision ( 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…The iron–sulfur cluster is an ancient and essential protein cofactor with various compositions and structures , and is widely distributed in bacteria , and mammals, , indicative of conserved biological evolution to some extent . The three major iron–sulfur clusters in organisms, Isc (iron–sulfur cluster), Nif (nitrogen fixation), and Suf (sulfur utilization factor), play significant roles on nucleic acid replication and repair, nitrogen fixation, and bacterial sulfur depletion processes. , Iron–sulfur clusters in mammals generally exist as [2Fe2S], [4Fe4S], and [3Fe4S] and participate in various physiological processes such as mitochondrial respiration, DNA replication, , and repair, ,, via the ligand binding of Fe atoms with cysteine/histidine residues. The [4Fe4S] cluster generally serves itself as an electron transfer switch involved in the redox process of DNA replication and repair.…”
Section: Introductionmentioning
confidence: 99%
“…The abundance and ubiquity of metalloproteins have attracted much scientific endeavors to understand the relationships between protein structures and functions [4,5], and translate that understanding into real-life applications [6,7]. While traditional molecular modeling approaches, such as classical molecular dynamics [8,9] and quantum mechanics/molecular mechanics (QM/MM) methods [10], have often been used to study these objectives, the usage of machine learning models has grown in popularity over the last decade [11], as metalloproteins can now be studied in a computationally inexpensive manner at a systems level. By designing and optimizing models to learn patterns and distinctions from training and validation data sets, these machine learning models can eventually predict the properties and behaviors of any new inputs (i.e., test sets).…”
Section: Introductionmentioning
confidence: 99%